A prospective study to evaluate the efficacies of low volume and high volume caudal epidural steroid injections in the treatment of lumbar degenerative disc disease - Sajeev, Suraj; Karuppal, Raju (International Journal of Research in Medical Sciences, 2017)
Background: To evaluate the efficacy of low volume corticosteroid injections in the treatment of radiculopathy associated with lumbar degenerative diseases by comparing with that of conventional high-volume injection and appreciate the advantages of the technique. Study was a prospective comparative study. Setting was the operating room. Methods: 52 patients, they were randomized into two groups. Among them, 27 had undergone caudal epidural steroid injection (CESI) with low volume and 25 with high volume injections of triamcinolone. Intervention of the study was caudal epidural steroid injection (CESI) to all patients in both groups. Low volume group received 5 ml and high-volume group received 15 ml diluted triamcinolone solution. They were evaluated with the visual analog scale, Oswestry low back disability questionnaire, short form 12, relief of claudication and neurological disability. Results: There was no statistically significant difference in the clinical improvement between the two groups. However, there are definite distinct advantages of low volume injection such as lesser pain at injection site and no complications that warrant admission. Conclusions: The low volume technique of CESI is superior to the traditional high-volume technique in this study. Despite earlier concepts that low volume injections failed to penetrate the proximal epidural spaces, present study conclusively proved that it is superior to high volume injections.